Rehabilitation and Reintegration of Libya Returnee-Migrants in Benin-City, Edo State, Nigeria. - Chinedu Ogbuze (Universitas Medan Area, 2022)
Migration from the global South to the North is a contemporary problem with a high number of casualties. This study examines the challenges of rehabilitation and reintegration of returnee migrants from Libya in Benin-city, Edo State, Nigeria. Maslow’s Human Needs theory and Push-Pull migration theory were adopted as a framework for the study. Primary data was collected through the use of semi-structured interview guide and non-participant observation. A total number of 20 oral interviews were conducted, which included 10 in-depth interviews with the returnees and 10 key informant interviews with the coordinators and stakeholders of the rehabilitation and reintegration programme in Benin-city, Edo State. Secondary sources included books, journals and Newspapers. Findings show that weak monitoring and evaluation, inadequate funding, stigmatization, politicization of the programme by the Edo State government officials and other stakeholders leading the reintegration programme, are factors that challenge the rehabilitation and reintegration of the returnees from Libya in Benin-City, Edo State, Nigeria. Among other things, the study recommended that effective monitoring and evaluation mechanism should be deployed, and collaboration with donor agencies and host nations by the Edo State government is also needed to improve funding and ensure sustainable reintegration of the returnees.